Serum micronutrient status, sleep quality and neurobehavioural function among early adolescents. Issue 17 (26th December 2021) - Ji, Xiaopeng; Compher, Charlene W; Irving, Sharon Y; Kim, Jinyoung; Dinges, David F; Liu, Jianghong
Abstract: Objective: To examine associations between serum micronutrients and neurobehavioural function and the mediating role of sleep quality in early adolescents. Design: In this cross-sectional study, peripheral blood samples were analysed for Fe and Zn levels. The Pittsburgh Sleep Quality Index and Penn Computerized Neurocognitive Battery were used to assess sleep quality and neurobehavioural function, respectively. The logistic/linear regressions and generalised structural equation modelling were performed to estimate the associations. Setting: Jintan, China Participants: In total, 226 adolescents (106 females) from the Jintan Child Cohort study. Results: Adolescents with low Fe (<75 μg/dl) (OR = 1·29, P = 0·04) and low Zn (<70 μg/dl) (OR = 1·58, P < 0·001) were associated with increased odds for poor sleep quality. Adolescents with low Fe and Zn were associated with fast (Fe: β = –1353·71, P = 0·002, Zn: β = –2262·01, P = 0·02) but less-accurate (Fe: β = –0·97, P = 0·04; Zn: β = –1·76, P = 0·04) performance on non-verbal reasoning task and poor sleep quality partially mediated the associations between low Fe/Zn and non-verbal reasoning ( P < 0·05). Additionally, low Fe was associated with a slower reaction on spatial processing task ( β = 276·94, P = 0·04), and low Zn was associated with fast ( β = –1781·83, P = 0·03), but error-prone performance ( β = –1·79, P = 0·04) on spatial processing ability and slower reaction speed ( β = 12·82, P = 0·03) on the attention task. We observed similar trends using a cut-off point of 75 μg/dl for low serum Zn, except for the association with attention task speed ( P > 0·05). Conclusion: Fe and Zn deficiencies may possibly be associated with poor sleep and neurobehavioural function among early adolescents. Poor sleep may partially mediate the relationship between micronutrients and neurobehavioural function.